NomadicBTS: Evolving cellular communication networks with software-defined radio architecture and open-source technologies. Issue 1 (1st January 2018) - Adetiba, Emmanuel; Matthews, Victor O.; John, Samuel N.; Popoola, Segun I.; Abayomi, Abdultaofeek
Abstract: Utilization of software-defined radio (SDR) and open-source technologies in the next evolution of cellular communication networks may significantly reduce the capital expenditure (CAPEX) and operating expenditure (OPEX) of mobile network operators in emerging economies. In this paper, a novel cellular communication architecture named NomadicBTS was proposed, designed, and prototyped based on SDR paradigm to achieve an efficient, dynamic, and cost-effective wireless communication. The architecture comprises of hardware front-end and software that are compatible with general-purpose processor. Open-source technologies were adopted to implement a proof-of-concept architype of the architecture. A prototype femtocell (of approximately 7.54-m cell radius) was set up and two different commercially available smart phones were used to scan, detect, and measure the strength and quality of radio signals that were transmitted by the NomadicBTS prototype. Experimentation results showed that the network signal is visible to the smart phones, and its strength and quality are sufficient for good transmission and reception of Short Messaging Services (SMS). Unlike the conventional cellular networks which are capital-intensive, the results obtained in this study provide a basis to deploy low-cost cellular communication networks for the underserved areas in developing countries.